THE INTERNAL CONTROL OF MANAGEMENT ACCOUNTING INFORMATION SYSTEMS OF THE STATE-OWNED ENTERPRISES IN INDONESIA - Dalimunthe, Abdul Rahman; Napitupulu, Ilham Hidayah; Situngkir, Anggiat (Archives of Business Research, 2018)
This article aims to examine the implementation of internal controls in management accounting information systems. Management accounting information system is used as a tool to generate relevant information in decision making. In order to make Management accounting information system progressed as expectations, the internal control is needed as a functioning controller of Management accounting information system in the organization. COSO Internal Control framework focuses on the effectiveness of information systems controls that will improve the quality of management accounting information system. This research uses descriptive analytic method, data collected by using questionnaire distributed to operations manager in 56 State Owned Enterprises. The findings shows that generally the internal control in the Management accounting information system in State Owned Enterprises (SOEs) has been in a good categorized, but there is still found some internal control weaknesses in SOEs, which is SOEs is less effective in assets controlling and data security controlling. Less good attention or less optimal of each SOEs in controlling its assets is known from the answers to the operational managers who said that is less good respondents’ attention in conducting assets inventory that is registered in the system physically.